(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The main aim of the present study was to analyzed andfind out the relationship between occupational stress and mental health amongworking women. Four hundred fifty working women as a teacher, nurse and clerkparticipated in study. Standardized Occupational Stress Index by Shrivastav andMental Health Inventory by Jagdish were used for data collection. To analyzethe data‘t’ test and (product moment) correlation technique were used. Resultsindicate that high occupational stress was found among nurses in comparison toclerks and teachers. Significant correlation found between occupation stressand mental health among working women.